Tracing source and evolution of suspended particles in the Rio Negro Basin (Brazil) using chemical species of iron - Allard, T.; Weber, T.; Bellot, C.; Damblans, C.; Bardy, M.; Bueno, G. [UNESP]; Nascimento, N. R. [UNESP]; Fritsch, E.; Benedetti, M. F. (Elsevier B.V., 2011)
Suspended solids found in porewaters obtained in waterlogged soil sequences that included representative laterite-podzol transitions, associated brooks and major rivers of the Rio Negro watershed (Brazil) were studied using electron paramagnetic resonance (EPR) and Fourier-transform infrared spectroscopies. The main goal was to ascertain sources and track the evolution of suspended matter using a ubiquitous chemical species, FeIII complexed to organic matter (FeOM). Three size fractions were separated by tangential-flow (ultra)filtration: particulate (>0.2 mu m), dense (P) and light (Ps), and colloidal (5 kD<Col.<0.2 mu m) fractions. Quantitative results were acquired for Col. and Ps fractions which are predominantly organic in nature.FeOM concentration (in parts per thousand dry weight) was determined to be relatively low in suspended solids found in black waters from podzol porewaters and brooks whereas in the main rivers it was several times higher. FeOM concentrations were also correlated with Fe(II)/Fe(III) ratios in solution; these ratios were high in podzol porewaters and low in the rivers. Considering that organic complexation of Fe(II) is minor when compared to that of Fe(III), two interpretations were proposed to account for the above observation. First, [FeOM] was assumed to be distributed along a mixing line, with the clear waters from laterites and the black waters from podzols being its end-members. Consequently, [FeOM] can be used to trace the source of suspended material. Second, dissolved Fe(II) from podzol areas was considered to be progressively oxidized as pore waters move towards the mainstream. According to this mechanism, iron is complexed by organic matter or precipitated as oxides, thus producing an evolution of colloidal matter. As a result of these mechanisms' action, both the high production of Fe(II) and organic matter at the waterlogged podzol-laterite transition areas are major factors affecting iron export in the Rio Negro watershed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Iron; Colloids; Organic matter; Amazon Basin; EPR; Podzol